PENGARUH MEDICAL TOURISM TERHADAP PEMINATAN LAYANAN RUMAH SAKIT INTERNASIONAL STUDI KASUS PRIMAYA HOSPITAL TANGERANG - Nuraini, Ridzka; Asri Kartini, Raden; Utami, Sri (STABN Raden Wijaya Wonogiri, 2025)
Medical tourism is increasingly becoming a strategic initiative in enhancing international hospital services, yet empirical evidence on its influence toward patient interest remains limited in Indonesia. This study aims to examine the effect of medical tourism on the interest in international hospital services, using Primaya Hospital Tangerang as a case study. Employing a quantitative causal design, the study involved 150 patients selected through purposive sampling. Medical tourism was treated as the independent variable, and interest in international hospital services as the dependent variable. Data were collected through Likert-scale questionnaires and documentation, followed by validity and reliability testing. Statistical analysis utilized classical assumption tests and simple linear regression. The findings indicate that medical tourism significantly and positively influences patient interest in international hospital services, with a regression coefficient of 0.916 and R² of 0.470. This implies that 47% of the variation in patient interest is explained by medical tourism factors such as hospital facilities, administrative services, interactive digital platforms, and destination appeal. The study concludes that a holistic medical tourism approach substantially boosts patient interest, suggesting that hospitals should improve not only medical quality but also non-medical service dimensions to compete in the global medical tourism market.